Remote work and long-term sickness absence due to mental disorder trends among Japanese workers pre/post COVID-19 - Yasuhiko Deguchi; Shinichi Iwasaki; Yuki Uesaka; Yutaro Okawa; Shohei Okura; Kunio Maekubo; Ayaka Matsunaga; Yuki Kageyama; Koki Inoue (PLoS ONE, 2025)
Aims The aim of this study was to ascertain whether there has been an increase in the number of workers with long-term sickness absence due to mental disorders (LTSA-MD) and determine the impact of remote work on new LTSA-MD cases. Methods A web-based questionnaire was sent to 2,552 company offices with 150 or more workers in Osaka Prefecture. Data were obtained on the number of workers with LTSA-MD between April 1, 2019, and March 31, 2020 (fiscal year 2019) and between April 1, 2020, and March 31, 2021 (fiscal year 2020), along with their MD diagnoses (adjustment disorder [AD], depressive disorder [DEP], etc.). The difference in the number of new LTSA-MD, LTSA-AD, and LTSA-DEP cases between the fiscal years was evaluated, as well as the number of LTSA-MD cases per 100 employees. An independent t-test was used to compare the groups. Results DEP was the most prevalent condition, followed by AD. The number of workers with LTSA-MD nominally decreased from fiscal 2019 to fiscal year 2020, with no significant difference. There were no significant differences between fiscal year 2020 and fiscal year 2019 regarding LTSA-MD, LTSA-AD, and LTSA-DEP in offices with and without a remote work model. Conclusions The number of non-public workers with LTSA-MD did not increase during the COVID-19 pandemic, with no significant difference observed between offices with and without a remote work model. This provides preliminary evidence of a potential protective effect of remote work against LTSA-DEP.